Reaching Hispanic Audiences: What Can We Do as Extension Educators? - Nick T. Place; Dilcia Toro (EDIS, 2019)
Hispanics are a major part of Florida's population, and it is critical that Cooperative Extension take steps towards addressing their educational needs. By focusing on their specific needs across the three phases of program development, extension educators will encounter greater success and impact with this important clientele group. This document is AEC-375, one of a series of the Agricultural Education and Communication Department, UF/IFAS Extension. Original publication date February 2006.